2009
DOI: 10.1007/s00417-009-1074-x
|View full text |Cite
|
Sign up to set email alerts
|

Drug reflux during posterior subtenon infusion of triamcinolone acetonide in diffuse diabetic macular edema not only brings insufficient reduction but also causes elevation of intraocular pressure

Abstract: At the time of STI-TA in DME, drug reflux of TA is a risk factor not only for insufficient reduction of edema, but also for postoperative IOP elevation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…15 Although not evaluated in this study, drug reflux following posterior subtenon injection has been demonstrated in another study to predict an increase in intraocular pressure. 16 …”
Section: Discussionmentioning
confidence: 99%
“…15 Although not evaluated in this study, drug reflux following posterior subtenon injection has been demonstrated in another study to predict an increase in intraocular pressure. 16 …”
Section: Discussionmentioning
confidence: 99%
“…In past studies of combination therapy of bevacizumab and triamcinolone acetonide, both drugs were administered by vitreous injection, which requires a bigger liquid volume (twice as much as that for single-drug therapy) and induces IOP elevation. In contrast, in our study, triamcinolone acetonide was administered through the subtenon space, which prevents cataract formation and IOP elevation if injected appropriately [14,22]. Thus, STTA/IVB combination therapy, which is different from IVTA/IVB therapy, might show better, safer, and longer-lasting results than IVB monotherapy for suppression of DME.…”
Section: Discussionmentioning
confidence: 57%
“…Before the administration of the drugs, the IOP was 15.6 ± 2.3 (range 11-20) mmHg in the STTA-treated eyes and 15.7 ± 2.8 (range [11][12][13][14][15][16][17][18][19][20] mmHg in the control eyes, and there was no significant difference between them (P = 0.927). After the initial IVB injection, the IOP in the STTA-treated eyes increased steeply and, after 24 weeks, significantly increased, while the IOP in the control eyes b Reduction ratio (refer to the text) in eyes with (black bar) and without (white bar) STTA.…”
Section: Alteration Of Iopmentioning
confidence: 63%
See 2 more Smart Citations